Cooling through barocaloric effect: A review of the state of the art up to 2022. (1st August 2022) - Cirillo, Luca; Greco, Adriana; Masselli, Claudia
Highlights: Barocaloric is an emerging cooling technology based on solid-state materials. Barocaloric is a potential ecofriendly alternative to vapor compression. A review of the thermodynamical cycles, materials and numerical models is presented. Future perspectives and lines of research are drawn. Abstract: Barocaloric is the more recent among the caloric technologies employing solid-state materials. The name derives from BaroCaloric Effect (BCE), the phenomenon responsible of changes in the material temperature following an adiabatic variation of the value of the applied hydrostatic pressure. Barocaloric is the technology for refrigerating and air conditions that lately earned the scene among the other caloric ones. Specifically, in the last 6 years the caloric route was turned towards barocaloric, with the consequence that it has an embryonic state, yet. The reason for such attraction lies in the promising giant temperature changes due to BCE exhibited by a wide number of materials in room temperature range. The present would be the first general review on barocaloric technology touching all the aspects of the related state of the art from a general point of view: the thermodynamic cycles, materials, numerical models, experimental devices and future perspectives.